2019
DOI: 10.3390/su11082325
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Multifunctional Zoning of Territorial Space: The Panxi Area of the Upper Yangtze River in China Case Study

Abstract: Multifunctional zoning is the primary basis for developing differentiated spatial planning systems and management policies of territorial spaces. The purpose of the paper is to generate an integrated multifunctional zoning scheme of the territorial space in Panxi by employing the functional significance assessment funded on the niche theory and its measurement models, in order to benefit the high efficiency land utilization and other socioeconomic development initiatives, such as the industrial poverty allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Not many international studies have used TSF as a specialized term. A few Chinese scholars have used TSF [14] and territorial space functional area and other related concepts in their research [15], but none of them provided a detailed definition. By comparing the connotation of territorial space [1] and land [16], it can be found that the meanings of territorial space and land are approximately the same in terms of nature and economy.…”
Section: Spatiotemporal Heterogeneity Of Land Use Superior Tsfs and Dynamic Coupling Between Land Use And Its Superior Tsfsmentioning
confidence: 99%
“…Not many international studies have used TSF as a specialized term. A few Chinese scholars have used TSF [14] and territorial space functional area and other related concepts in their research [15], but none of them provided a detailed definition. By comparing the connotation of territorial space [1] and land [16], it can be found that the meanings of territorial space and land are approximately the same in terms of nature and economy.…”
Section: Spatiotemporal Heterogeneity Of Land Use Superior Tsfs and Dynamic Coupling Between Land Use And Its Superior Tsfsmentioning
confidence: 99%
“…With the maturity of agricultural multifunction theory and the proposal of sustainable development, the multifunctional theory has gradually expanded from the agricultural field to other areas such as territorial multifunction [25,26]. e territorial function is the combined functionality of specific regions in the sustainable development of natural ecosystems and activities for human production and life [27,28], including urban territorial function and rural territorial function. Wilson pointed out that multifunctional theory can be used not only in agriculture but also in rural transformation and development, especially in describing the population, industry, environment of rural areas, and thought that the theory of rural multifunction is feasible in less developed countries or regions [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the research on the quality of territorial space utilization in China started late, it is developing rapidly. In the early days, some scholars studied intensive land use and land use optimization from the perspective of ecological civilization, and some scholars conducted zoning research on the multi-functionality of land space [3][4][5]. In recent years, there have been many research results on the comprehensive evaluation of the quality of territorial space utilization based on the "production-ecology-ecology" space and function [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%